1981
DOI: 10.2355/isijinternational1966.21.862
|View full text |Cite
|
Sign up to set email alerts
|

Melting Property of MgO Containing Sinter

Abstract: SynopsisThe solution property of Mg0 containing materials into the CaOFe203 system and the melting property of Mg0 containing sinter during reduction were investigated. The results obtained are summarized as follows:(1) The formation of high viscosity silicate and magnetite prevents the homogenization of slag and therefore, Cr slag and Ni slag remain unslagged. The formation of dicalcium ferrite prevents the dissolution of periclase into the CaO-Fe203 system.(2) During reduction unslagged Mg0 makes the shell o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Adding MgO into sinter is considered to be a popular counter measure to cope with usage of high Al 2 O 3 ores [1][2][3]. The purpose of adding MgO is mainly to prevent the worsening fluidity and desulphurisation ability of blast furnace slag and permeability in dripping zone caused by usage of high A1 2 O 3 ores [4][5][6][7]. Consequently, both Al 2 O 3 and MgO content in sinter increase and MgO/Al 2 O 3 changes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adding MgO into sinter is considered to be a popular counter measure to cope with usage of high Al 2 O 3 ores [1][2][3]. The purpose of adding MgO is mainly to prevent the worsening fluidity and desulphurisation ability of blast furnace slag and permeability in dripping zone caused by usage of high A1 2 O 3 ores [4][5][6][7]. Consequently, both Al 2 O 3 and MgO content in sinter increase and MgO/Al 2 O 3 changes.…”
Section: Introductionmentioning
confidence: 99%
“…For the effect of MgO, some researchers believed that increasing MgO content would improve softening temperatures because the high melting point substance containing MgO could increase the melting temperature of slag [25][26][27]. However, other researchers found that MgO did not significantly affect softening properties of sinter [6,23,28]. The disparity of the results among these literatures on effects of MgO and Al 2 O 3 in sinter showed that the roles of MgO and Al 2 O 3 in softening-melting process have not been reached consensus.…”
Section: Introductionmentioning
confidence: 99%
“…Since adding dolomite to the blast furnace will bring a series of adverse effects [7][8][9], magnesium-containing fluxes are usually added during the sintering process. As for the effects of magnesium flux on the sintering process, previous studies have shown that MgO has a negative effect on the strength and reducibility index and a positive effect on the reduction degradation index of the sinter [10][11][12][13][14][15]. It can be seen that the reaction behavior of MgO is closely related to the quality index of sintering production.…”
Section: Introductionmentioning
confidence: 95%
“…Some experts believe that raising the MgO content in sinter will raise the melting temperature of slag since magnesium oxide-containing minerals have a high melting point [13,14]. Other research, on the other hand, has found that magnesium oxide has no effect on sinter softening properties [15][16][17]. When analysing the impact of MgO on the performance of sinter, researchers created the relative value concept of 'MgO/Al 2 O 3 ' to more precisely identify the acceptable MgO content in sinter.…”
Section: Introductionmentioning
confidence: 99%